Singing of Deportees and Political Prisoners: Aspect of Liminality - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2021)
The number of socially charged songs appearing during the period of prewar and postwar deportations, and political imprisonments seems truly amazing. Singing and song composition in exile or imprisonment is difficult to conceive, since the harsh reality seems incompatible with singing. This article aims at elucidating the peculiar ritual character of singing in the exile while employing the concept of liminality introduced and elaborated by anthropologists (Victor Turner and Arnold van Gennep before him). This concept could at least partly explain this rise in creativity among the deportees and political prisoners. Although there are numerous testimonies of the exile conditions suppressing the incentives to sing, opposite situations seem also having been frequent enough: singing helped people to settle somehow in the foreign and harsh environment. In the second chapter, the concept of liminality and communitas by Victor Turner is introduced in more detail. Similarly, the author maintains that songs were meant to “ritually” recreate those things that had been destroyed under the curse of deportation. The third chapter presents a discussion of the songs by the deportees and political prisoners. These songs are characterized by clear notion of the singers’ martyrdom. Motives of victimization, self-sacrifice and offering of sufferings are directly related to this notion. These sacrifices are deemed meaningful – they are believed to serve the cause of the national freedom; belief in the soul’s immortality and superiority is also strong. Motive of promising oneself or promising one’s heart to Lithuania is voiced. Sometimes striving for freedom is depicted as looking forward to the fulfilment of love. Impressive metaphors of deportation, such as travel, wandering, or hiding in the deep well could be pointed out. Often enough the deportee or political prisoner reflects upon his / her non-existence. Along with such motives, various testimonies regarding the particular value ascribed to these songs and the special effect they allegedly had on the listeners, etc. are also quoted in the article. The author of the article aspires to analyze the legacy of deportation, on the one part, as a text, and on the other part, as a rise in creativity resulting from communal and individual attitude. Therefore, material of this interdisciplinary study includes both the songs of deportees and political prisoners and the testimonies by the singers reflecting upon their own perception and understanding of their singing. On the one hand, these songs considerably differ from the traditional folksong poetic; on the other hand, their melodies are close to the new style of folksongs, thus their uniqueness should be primarily attributed to their origins. Therefore, it seems expedient to use a broader context of singing under the harsh conditions of exile or imprisonment, which considerably substantiates the value of these songs. Deportation is fraught with most painful losses shrouded with “in-between” existence – thus, a model liminal situation. Moreover, singing in exile helps to purify the very existence of the person finding himself or herself in this state of liminality, and thus can be reasonably considered a special attitude of the deportee. The individual as a whole is existentially incorporated into the symbolically adorned ritual process of solving the problems of life and death, which stands out in the songs of deportees and political prisoners. The community celebrations and gatherings helped to enhance the identity of the deportees finding themselves in the state of liminality. While singing, although generally a rare thing in the course of both celebrations and everyday routine, provided an important expression of vitality and spiritual freedom.